Development of New Products and Energy Consumption in Industrial Production: Relationship and Evidence From China - Tang, Erzi (Frontiers in Energy Research, 2022)
Will energy consumption decrease when producers implement some innovative activities in industrial production? As a special but important innovation, how development of new products impact energy consumption is a valuable issue. This paper proposes a model to analyze the relationship of energy consumption and development of new products and finds that development of new products and production probably increase total energy consumption and energy intensity by output simultaneously since the productivity of producing new products may be lower than those existing goods with mature processes in industrial production. Producers develop new products with cleaner technology by saving energy or/and with higher initial productivity is possible to decrease energy consumption. After theoretical analysis, this paper tests empirically the correlation between development of new products and energy consumption by using 2016-2019 data of Chinese industry and reveals that development of new products and production increased total energy consumption and energy intensity by output in industrial production, but decreased the usage and intensity of a special final energy product as gasoline. These findings indicate that the Chinese industrial sector developed new products with cleaner technology by only saving gasoline. The effect of total energy saving by implementing innovative activities with new products development in industrial production was very limited in China. Chinese industry consumes huge amounts of energy and spends a lot of money on development of new products, policy makers with the vision of innovative and green development need to balance development of new products and energy consumption.